Numerical Investigation of Influence of Air and Fuel Dilution for Open Furnace MILD Combustion Burner - M. M., Noor; Wandel, Andrew P. (2012)
Climate change and greenhouse gases (GHG) have become one of the priorities for today’s intergovernmental issues. Reducing pollution and recycling the GHG are new challenges for the combustion community. The new technology Moderate or Intense Low oxygen Dilution MILD) combustion is one of the best alternatives for high thermal efficiency and low pollution combustion. This paper discusses the modelling of MILD combustion in an open furnace using FLUENT. Exhaust gas recirculation (EGR) was utilised to increase the combustion thermal efficiency by the reuse of the heat in the flue gas. The combustion chamber is enclosed to capture the flue gas for EGR. The oxygen dilution and pre-heating of the oxidiser which are vital for operating in the MILD regime can be achieved by utilising EGR. The top of the chamber will be the opening for exhaust gas release. The ratios of EGR, fuel and air inlet velocity were numerically studied for their effect on achieving MILD combustion in an open furnace. Higher dilution ratios produce lower NOx emissions and more readily achieve the MILD condition.